Seismic damage estimation of in-plane regular steel/concrete composite moment resisting frames. (15th May 2016) - Kamaris, George S.; Skalomenos, Konstantinos A.; Hatzigeorgiou, George D.; Beskos, Dimitri E.
Highlights: The seismic damage estimation of composite frames is investigated. Appropriate empirical expressions of four well-known damage models are provided. Comparisons between the proposed method and dynamic inelastic analyses results are presented. Abstract: Simple empirical expressions to estimate maximum seismic damage on the basis of four well known damage indices for planar regular steel/concrete composite moment resisting frames having steel I beams and concrete filled steel tube (CFT) columns are presented. These expressions are based on the results of an extensive parametric study concerning the inelastic response of a large number of frames to a large number of ordinary far-field type ground motions. Thousands of nonlinear dynamic analyses are performed by scaling the seismic records to different intensities in order to drive the structures to different levels of inelastic deformation. The statistical analysis of the created response databank indicates that the number of stories, beam strength ratio, material strength and ground motion characteristics strongly influence structural damage. Nonlinear regression analysis is employed in order to derive simple formulae, which reflect the influence of the aforementioned parameters and offer a direct estimation of the damage indices used in this study. More specifically, given the characteristics of the structure and the ground motion, one can calculate the maximum damage observed in column bases and beams. Finally, three examples serve to illustrate the use of the proposed expressions and demonstrate their accuracy and efficiency.